2017
DOI: 10.1002/pro.3148
|View full text |Cite
|
Sign up to set email alerts
|

Monobodies and other synthetic binding proteins for expanding protein science

Abstract: Synthetic binding proteins are constructed using nonantibody molecular scaffolds. Over the last two decades, in‐depth structural and functional analyses of synthetic binding proteins have improved combinatorial library designs and selection strategies, which have resulted in potent platforms that consistently generate binding proteins to diverse targets with affinity and specificity that rival those of antibodies. Favorable attributes of synthetic binding proteins, such as small size, freedom from disulfide bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 80 publications
1
121
1
Order By: Relevance
“…Similarly, BCL-2 binding Affimers themselves could be elaborated for therapeutic or diagnostic use. 34,66 Of potentially equal significance is the observation that non-canonical folds can substitute for native folds in peptide/protein based inhibitors of PPIs 67,68 ; this is reminiscent of the use of a β-hairpin to mimic an α-helix for p53/hDM2 inhibition. 69,70 In contrast to those studies, the sequences identified here were obtained under selection pressure, and this poses the question: do BCL-2 family proteins function in cells through molecular modes of interaction other than the canonical α-helix/cleft motif observed to date?…”
Section: Discussion (Without Subheadings)mentioning
confidence: 99%
“…Similarly, BCL-2 binding Affimers themselves could be elaborated for therapeutic or diagnostic use. 34,66 Of potentially equal significance is the observation that non-canonical folds can substitute for native folds in peptide/protein based inhibitors of PPIs 67,68 ; this is reminiscent of the use of a β-hairpin to mimic an α-helix for p53/hDM2 inhibition. 69,70 In contrast to those studies, the sequences identified here were obtained under selection pressure, and this poses the question: do BCL-2 family proteins function in cells through molecular modes of interaction other than the canonical α-helix/cleft motif observed to date?…”
Section: Discussion (Without Subheadings)mentioning
confidence: 99%
“…Thus, many positions of the frankenbody can be mutated without destroying its functionality, demonstrating great potential for further evolution. We therefore anticipate the HA frankenbody will be a useful new imaging reagent to complement the growing arsenal of live-cell antibody-based probes 23,[49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…We have achieved success with a number of different formats including scFv intrabodies, FN3s, and DARPins. Other scaffolds may also work, provided that they are small, fold efficiently in the reducing cytosolic environment, and exhibit high affinity (low µM to nM) and specificity towards the intended target (Sha, Salzman, Gupta, & Koide, 2017). There have been several reports describing successful fusions between DBPs and truncated E3 ubiquitin ligases (Caussinus et al, 2011; Portnoff et al, 2014; Shin et al, 2015).…”
Section: Strategic Planningmentioning
confidence: 99%